What’s the social agents thinking about the role of competencies in Higher Education? Social Education Degree - Gómez Sánchez, Tania Fátima; Rumbo Arcas, Maria Begoña (Revista Complutense de Educación, 2017)
The utilitarian perspective has been based on the university as an incubator for specialized professionals. Curricula and degrees have been focused on the needs of the market. The European Higher Education Area (EHEA) has promoted the education policies which have been focused mainly in these concerns in the process of convergence of higher education. However, there are few research and studies about competences learning and labor market needs in Higher Education (Foncubierta, Perea & Siles, 2016; Aragón et al., 2015), particularly in the Spanish context and from a pedagogical and educational perspective. Consequently, our aim is to bring us closer to policy actions based on competences model as an impulse to the employability of graduates. For that purpose, we have carried out a qualitative, phenomenological and descriptive study. The information sources used were social agents. As a result, social agents have seen EHEA changes as structural transformations. This perspective is evidencing a certain distance, which translates into a lack of knowledge of the competences of the degree. They demand the need for a greater dialogue between university institutions and society, and a better definition of the professional role. Therefore, we can’t see an awareness raising about the degree value. Even more, we can’t observe a dialogue between the university and society. Thereby, the competences model is not connecting the university with the labor market. It is revealing a break between social agents and higher educational policies.